Down-regulation of Myeloid Cell Leukemia-1 through Inhibiting Erk/Pin 1 Pathway by Sorafenib Facilitates Chemosensitization in Breast Cancer - Ding, Qingqing; Huo, Longfei; Yang, Jer-Yen; Xia, Weiya; Wei, Yongkun; Liao, Yong; Chang, Chun-Ju; Yang, Yan; Lai, Chien-Chen; Lee, Dung-Fang; Yen, Chia-Jui; Chen, Yun-Ju Rita; et al. (Cancer research (Chicago, Ill.), 2008)
Myeloid cell leukemia-1 (Mcl-1), a Bcl-2–like antiapoptotic protein, plays a role in cell immortalization and chemoresistance in a number of human malignancies. A peptidyl-prolyl cis/trans isomerase, Pin1 is involved in many cellular events, such as cell cycle progression, cell proliferation, and differentiation through isomerizing prophosphorylated substrates. It has been reported that down-regulation of Pin1 induces apoptosis, and that Erk phosphorylates and up-regulates Mcl-1; however, the underlying mechanisms for the two phenomena are not clear yet. Here, we showed that Pin 1 stabilizes Mcl-1, which is required for Mcl-1 posphorylation by Erk. First, we found expression of Mcl-1 and Pin1 were positively correlated and associated with poor survival in human breast cancer. We then showed that Erk could phosphorylate Mcl-1 at two consensus residues, Thr 92 and 163, which is required for the association of Mcl-1 and Pin1, resulting in stabilization of Mcl-1. Moreover, Pin1 is also required for the up-regulation of Mcl-1 by Erk activation. Based on this newly identified mechanism of Mcl-1 stabilization, two strategies were used to overcome Mcl-1–mediated chemoresistance: inhibiting Erk by Sorafenib, an approved clinical anticancer drug, or knocking down Pin1 by using a SiRNA technique. In conclusion, the current report not only unravels a novel mechanism to link Erk/Pin1 pathway and Mcl-1–mediated chemoresistance but also provides a plausible combination therapy, Taxol (Paclitaxel) plus Sorafenib, which was shown to be effective in killing breast cancer cells. [Cancer Res 2008;68(15):6109–17]